Mechanical thrombectomy with 'ADAPT' technique by transcervical access in acute ischemic stroke. Issue 6 (December 2015) - Castaño, Carlos; Remollo, Sebastian; García, Maria Rosa; Hidalgo, Cristina; Hernández-Perez, Maria; Ciorba, Mihaela
Background: The mechanical thrombectomy (MT) for endovascular clot retrieval has dramatically improved successful revascularization and clinical outcome in selected acute stroke patients. MT is typically performed via a transfemoral approach, but catheterization of the occluded vessel can be problematic in cases of extensive vessel tortuosity. We describe a case of MT with the 'ADAPT' technique by direct carotid access due to an inability to catheterize the ICA by a transfemoral approach for acute cerebral ischemia in the setting of left MCA occlusion. Excellent angiographic and good clinical results were obtained without any complications. Case report: An 80-year-old woman was admitted with a stroke by occlusion of the left MCA, with an NIHSS: 11, and an ASPECT: 7 in the CT. Under sedation a transfemoral angiography was performed, but after multiple attempts, it was impossible to make a stable catheterization of the left CCA. A transcervical approach was pursued. With ultrasound guidance the CCA was catheterized. Using the 'ADAPT' technique, we performed a successful MT. Post-procedure angiography (at 14 minutes) demonstrated recanalization of the entire left MCA (TICI: 3), without complications. The carotid access point was closed with a percutaneous closure. Control TC at 24 h showed a slight hypodensity in the left lenticular nucleus, and loss of gray-white matter differentiation in the adjacent cortex. Neurologically, the patient presented with progressive improvement. At discharge, she had an NIHSS: 0, mRS: 0 and Barthel: 100. Conclusions: MT by direct carotid access is an effective alternative technique in those cases where it is not accessible by a transfemoral approach.